Sexually Transmitted Infections (STIs) Control Strategies in Georgia - Kajrishvili, Marine; Lomtadze, Lili; Kakiashvili, David (European Scientific Journal, ESJ, 2017)
Epidemiological indicators in Georgia suggest that the number of STIs cases had been on the increase prior to 1998. Although there has been a recent decline from 1998 to 2000 in STIs cases due to the successful control and management of STIs in Georgia, the once extinct disease is now an epidemiologic concern. The problems and constraints facing the country are: • The concentration of STIs transmission along the Turkish border. • The lack of a specialized national STIs control service and need for preventive services to be upgraded to deal with the STIs situation. • Concentration of intense transmission of STIs with poor access to existing health services resulting in high and underreported morbidity. • Under-equipped, under-supplied and under-staffed health facilities and under-trained and under- paid public health personnel resulting in inadequate quality of disease management and prevention. • Poor capacities for early diagnosis and prompt treatment of STIs resulting in inadequate coverage of people being at risk of STIs. • Lack of surveillance particularly at the periphery resulting in untrue reflection of the extent of STIs problem in the country. • Lack of communities’ knowledge and skills to prevent themselves from getting STIs resulting in a rather scanty use of personal protective measures. • Limited resources invested by the Government and external donors resulting in lack of proper funding to cope with the STIs problem. The authors suggest new strategies and research in the field of disease management.